PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PNS PADA BIRO PEREKONOMIAN DAN BIRO ADBAG DI KANTOR GUBERNUR SUMATERA UTARA - Manik, Enjelia; Saputra, Hendra (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This quantitative study aims to analyze the effect of leadership style and organizational culture on employee performance, with organizational culture as a mediating variable. The sample consisted of 64 civil servants in the Economic Bureau and Development Administration Bureau (Adbang) of the Office of the Governor of North Sumatra Province. Data were collected through questionnaires and analyzed with multiple regression and mediation tests using SPSS. The results showed: (1) leadership style has a positive-significant effect on performance; (2) organizational culture has a positive-significant effect on performance; (3) leadership style influences organizational culture; and (4) organizational culture acts as a mediator in the leadership style-performance relationship. These findings confirm the need to strengthen transformational leadership style and organizational culture values to improve employee performance.